Pengaruh Jaminan Rasa Aman dan Lokasi terhadap Minat Transaksi di Bank Syariah Pada Masyarakat Aek Kota Batu - Lindung Pratama; Muhammad Lathief Ilhamy Nasution (Jurnal Informatika Ekonomi Bisnis, 2023)
The purpose of this study is to examine the effect of security guarantees and location on interest in transactions with Islamic banks in the people of Aek Batu City. The research method used in this case is quantitative research. The data in this study are primary data in the form of questionnaires that have been distributed to 100 communities. Sample the method used is purposive sampling technique. Hypothesis testing was carried out using SPSS 20.0 for windows by testing the independent variables namely Guaranteed Sense of Security and Location and the dependent variable namely Interest in Transactions.The normality test using the Kolmogrov-Smirnov method obtained a result of 0.699, which means it is greater than 0.05, so it can be concluded that the normality test on the variables Assurance of Security, Location and Interest in Transactions can be said to be normally distributed. The results of the regression analysis in the first model show that the Guaranteed Sense of Security and Location variables have a positive and significant effect on Transaction Interest. The Guaranteed Sense of Security variable has a coefficient value of 0.593 and the Location variable has a coefficient value of 0.084. Based on the calculation results, it can be concluded that tcount is greater than the value of ftable 35.479> 2.69, so H0 is rejected and Ha is accepted, so there is a significant influence between the Guaranteed Sense of Security and Location variables on Interest in Transactions at Sharia Banks in the Aek Community of Batu City.